The Relationship Between Anemia in Pregnant Women and The Incidence of Preeclampsia in Indonesia : A Systematic Review - Pirlina Umiastuti; Sri Umijati; Raissa, Safira; Muhammad Fadhil; Khansa Raihani; Emyrazel Fahdizar; Neissya Nastiti; Mariska Nuriana; Siti Aria; Shabrina Nur Imanina (Universitas Airlangga, 2024)
Preeclampsia is the biggest cause of morbidity and mortality worldwide and the second most common cause of maternal death in Indonesia. One of the highest risk factors for preeclampsia is anemia, so this study aimed to conduct a systematic review of the relationship between anemia in pregnant women and the incidence of preeclampsia. This research was an analytic type with a systematic review method from previous research with an observational case-control approach design with secondary data sources. The data were obtained from the results of previous research with a literature time limit of the last 5 years (2018–2022). This study used databases from Google Scholar, Pubmed, ScienceDirect, Garuda, and Summon Universitas Airlangga. The search yielded 2161 studies; after eliminating 439 duplicates, 1732 remained. After exclusion based on titles and abstracts, 36 studies remained, which were screened in full text. Finally, 8 studies were eligible and included in the review. Four studies showed a relationship between anemia in pregnant women and the incidence of preeclampsia, while four other studies showed no relationship. The prevalence of anemia in pregnant women in Indonesia ranges from 13.27% to 80.8%, with an average of 44.1%. Ages at risk for preeclampsia in Indonesia are pregnant women aged <20 years and >35 years. There is a relationship between anemia in pregnant women and the incidence of preeclampsia in Indonesia. Therefore, anemia can be a risk factor for preeclampsia.